Chitosan based hybrid materials used for wound healing applications- A short review. Issue 7 (2nd May 2020) - Ali Khan, Zulfiqar; Jamil, Shahrin; Akhtar, Amna; Mustehsan Bashir, Muhammad; Yar, Muhammad
Abstract: Various kinds of materials are used for wound healing. But natural polymers are more effective in wound healing as compare to synthetic polymers. Chitosan being a natural biopolymer exhibit various biological properties like biocompatibility, biodegradability, and many other good properties which makes it convenient to use for wound healing application. Different types of chitosan based hybrid materials are used to prepare wound healing nanocomposites, hydrogel sheets, membranes, films, sponges and other hybrid composites using various techniques. This review highlighted the formulation and biological evaluation of various chitosan based hybrid materials as wound dressing. GRAPHICAL ABSTRACT: Highlights: Chitosan has been examined for healing of wound in biomedical applications. This contributes to the structuring process in tissue. This polymer increases the tissue regeneration thus facilitating skin tissue engineering. Summarizes application of chitosan based hybrid materials in healing of wound.